2014
DOI: 10.1186/1472-6963-14-276
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS status disclosure increases support, behavioural change and, HIV prevention in the long term: a case for an Urban Clinic, Kampala, Uganda

Abstract: BackgroundDisclosure of HIV status supports risk reduction and facilitates access to prevention and care services, but can be inhibited by the fear of negative repercussions. We explored the short and long-term outcomes of disclosure among clients attending an urban HIV clinic in Uganda.MethodsQualitative semi-structured interviews were administered to a purposeful sample of 40 adult HIV clients that was stratified by gender. The information elicited included their lived experiences and outcomes of disclosure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 21 publications
2
69
0
1
Order By: Relevance
“…Studies in both rural and urban settings across sub-Saharan Africa have shown disclosure of HIV-positivity to be associated with positive outcomes including increased social support (Maman et al, 2003; Ogoina et al, 2015), reduced internalized stigma (Geary et al, 2014), improved mental health (King et al, 2008), and safer sexual behaviors (Rujumba et al, 2012). Other research in the region associates disclosure to sexual partners with increased understanding and support (Medley, Garcia-Moreno, McGill, & Maman, 2004; Obermeyer et al, 2011), trust (Atuyambe et al, 2014; King et al, 2008), and HIV care uptake (Deribe, Woldemichael, Wondafrash, Haile, & Amberbir, 2008; King et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Studies in both rural and urban settings across sub-Saharan Africa have shown disclosure of HIV-positivity to be associated with positive outcomes including increased social support (Maman et al, 2003; Ogoina et al, 2015), reduced internalized stigma (Geary et al, 2014), improved mental health (King et al, 2008), and safer sexual behaviors (Rujumba et al, 2012). Other research in the region associates disclosure to sexual partners with increased understanding and support (Medley, Garcia-Moreno, McGill, & Maman, 2004; Obermeyer et al, 2011), trust (Atuyambe et al, 2014; King et al, 2008), and HIV care uptake (Deribe, Woldemichael, Wondafrash, Haile, & Amberbir, 2008; King et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…12 Failure to disclose has been attributed to fear of abandonment, broken relationships, physical and emotional abuse, discrimination and loss of economic support. 2 Despite these disclosure-related fears, studies from both developed and developing countries [2][3][4][5][6][7] , Nigeria inclusive [8][9][10][11][12][13] , have revealed predominant positive or supportive reactions to disclosure, with 50-100% of sexual partners eliciting positive reactions following disclosure. The few reports of negative reactions such as disruption of relationships, violence and discrimination were more commonly reported among unmarried sexual partners and sero-discordant couples, as well as among people from low economic status and in those with history of violence in their relationships.…”
Section: Introductionmentioning
confidence: 99%
“…This is largely because stigma hinders uptake of HIV testing, a critical requirement for access to HIV treatment. In a study conducted in an urban clinic in Kampala, Uganda, authors showed that HIV status disclosure increase support, behavioural change and, HIV prevention in the long term (Atuyambe, Ssegujja, Ssali, Tumwine, Nekesa, Nannungi, Ryan & Wagner, 2014). The major reasons for termination of employment among HIV infected people were psychological one, not physical or symptoms-associated conditions (Vitry-Henry, Pénalba, Beguinot, & Deschamps, 1999).…”
Section: Introductionmentioning
confidence: 99%